Australian wheat production expected to decrease by the late 21st century. (15th January 2018) - Wang, Bin; Liu, De L.; O'Leary, Garry J.; Asseng, Senthold; Macadam, Ian; Lines‐Kelly, Rebecca; Yang, Xihua; Clark, Anthony; Crean, Jason; Sides, Timothy; Xing, Hongtao; Mi, Chunrong; et al.
Abstract: Climate change threatens global wheat production and food security, including the wheat industry in Australia. Many studies have examined the impacts of changes in local climate on wheat yield per hectare, but there has been no assessment of changes in land area available for production due to changing climate. It is also unclear how total wheat production would change under future climate when autonomous adaptation options are adopted. We applied species distribution models to investigate future changes in areas climatically suitable for growing wheat in Australia. A crop model was used to assess wheat yield per hectare in these areas. Our results show that there is an overall tendency for a decrease in the areas suitable for growing wheat and a decline in the yield of the northeast Australian wheat belt. This results in reduced national wheat production although future climate change may benefit South Australia and Victoria. These projected outcomes infer that similar wheat‐growing regions of the globe might also experience decreases in wheat production. Some cropping adaptation measures increase wheat yield per hectare and provide significant mitigation of the negative effects of climate change on national wheat production by 2041–2060. However, any positive effects will be insufficient to prevent a likely decline in production under a high CO2 emission scenario by 2081–2100 due to increasing losses in suitable wheat‐growing areas. Therefore, additional adaptation strategies along with investment in wheat production are needed to maintain Australian agricultural production and enhance global food security. This scenario analysis provides a foundation towards understanding changes in Australia's wheat cropping systems, which will assist in developing adaptation strategies to mitigate climate change impacts on global wheat production. Abstract : This study addresses how future climate change impacts wheat growth in areas across Australian wheat belt, how wheat yield per hectare would change with/without adaptation options and how national wheat production would response to future climate change when autonomous adaptation options are adopted. Our results show that future climate change benefits South Australia and Victoria but has adverse effects on Queensland. Adaptations increase wheat yield and provide mitigation of the negative effects of climate change on national production by 2050s; however, these positive effects are insufficient to prevent a likely decline in production under RCP8.5 by 2090s.